Assessment of knowledge and attitude among postnatal mothers towards childhood vaccination in Malaysia. Issue 11 (2nd November 2019) - Balbir Singh, Helvinder Kaur; Badgujar, Vishal Bhagwan; Yahaya, Rose Suzila; Abd Rahman, Santibuana; Sami, Farheen Mohd; Badgujar, Sangeeta; Govindan, Subhashini Nair; Ansari, Mohammed Tahir
ABSTRACT: Aim : Mothers knowledge and attitude toward childhood vaccination influence uptake is the most adequate tool and preventive aspects to infectious disease epidemics. The present study assesses and measures knowledge and attitude of postnatal mothers toward vaccination. Methods and results : The present study adopted a cross-sectional study design, whereby 200 postnatal mothers were identified during their postnatal visit to clinics. The subjects were accessed using questionnaire to assess the level of knowledge and attitude of mothers regarding vaccination. The objectives were to study the level of knowledge, the attitude, and to find the association between knowledge and attitude of the study subjects. The data were analyzed using SPSS version 16. The results was analyzed through chi-square test. The association between age ( p = .031), education ( p = .021), occupation ( p = .013), and knowledge score toward vaccination was found to be statistically significant. However, ethnicity ( p = .127), employment ( p = .197), and mode of delivery ( p = .750) toward mothers vaccination knowledge were not significant for the study. Mothers education, age, and occupation were found to be associated with attitude toward childhood vaccination. No association was found between ethnicity, employment, and mode of delivery with attitude of childhood vaccination. Conclusion : More than half of the studied mothers had good knowledge scores on vaccination, more than two-thirds of the studied mothers had good attitude scores on vaccination. However, the religious misconception and fear of autism was the main cause of vaccine resistance in Malaysia.